Effect of cholestyramine on the fecal excretion of intravenously administered cholesterol-4-(14)C and its degradation products in a hypercholesterolemic patient - Moore, Richard B. (1968)
The effect of cholestyramine on the fecal excretion of bile acids and neutral sterols was measured in a hypercholesterolemic patient on a low fat, high polyunsaturated fatty acid-containing diet after the intravenous injection of cholesterol-4-(14)C. A significant (16%) lowering of serum cholesterol concentration was accompanied by a 3.2-fold increase in fecal bile acid excretion but no change in neutral sterol output. The increased bile acid loss was adequate to account for the observed fall in serum cholesterol level. The implications of these findings were discussed.